2013
DOI: 10.1186/1471-244x-13-309
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and associated risk factors among persons with type-2 diabetes mellitus without a prior psychiatric history: a cross-sectional study in clinical settings in urban Nepal

Abstract: BackgroundDiabetes is a growing health problem in South Asia. Despite an increasing number of studies exploring causal pathways between diabetes and depression in high-income countries (HIC), the pathway between the two disorders has received limited attention in low and middle-income countries (LMIC). The aim of this study is to investigate the potential pathway of diabetes contributing to depression, to assess the prevalence of depression, and to evaluate the association of depression severity with diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
66
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 55 publications
14
66
3
Order By: Relevance
“…However, in some studies, women and married people are reported to be at a higher risk of depression. 18,21 In this study, those over 50 years of age, having low education level, unemployed, having three or more children and married to a husband with lower education level were determined to be at a greater risk of depression. The participants with three or more children were found to be at risk of depression 1.848 times more than were those with two or fewer children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some studies, women and married people are reported to be at a higher risk of depression. 18,21 In this study, those over 50 years of age, having low education level, unemployed, having three or more children and married to a husband with lower education level were determined to be at a greater risk of depression. The participants with three or more children were found to be at risk of depression 1.848 times more than were those with two or fewer children.…”
Section: Discussionmentioning
confidence: 99%
“…In Niraula et al's (2013) study, the prevalence of depression among people with diabetes was found as 40.3%. 18 In a systematic review designed to estimate the prevalence of clinically depressed patients with Type II diabetes, Ali et al (2006) found that the prevalence of depression was significantly higher among patients with type 2 diabetes (17.6%) than those without diabetes (9.8%). They also found that the prevalence among females with diabetes (23.8%) was higher than their male counterparts with diabetes (12.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted across the world unanimously agree that, the depression is a major mental health problem in adolescents with type 1 diabetes. Dusan et al reports the prevalence to be 38.5%, 4 Niruala et al reports 40.3%, 11 Hood et al reports 15.2%, 6 Sendela J et al reports 17%, 12 and Silversetin J reports that depression is two times more common in subjects with type 1 diabetes compared to type-2 diabetes. 5 This wide variation in the prevalence across the studies may be due to variety of scales available and differences in the modes of administration.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Results were for anxiety (56.7%) and depression (53.1%) in women group who was 18-34 years [14]. Niraula et al [15] showed in 385 patients with diabetes and clinical depression was 40.3% of the total sample. Among those depressed patients, 48.2% were female and 31.7% were male.…”
mentioning
confidence: 99%
“…11% of participants resulted positive for depression. Results showed that 21% of participants had scores for an anxiety disorder and, finally, 20.7% reported eating disorder [15]. De Ornelas et al in 2013 [16], reported 210 patients who were evaluated and divided in two groups, patients with Type 1/2 diabetes.…”
mentioning
confidence: 99%